Cyclodextrin-Based Polymer-Supported Bacterium for the Adsorption and in-situ Biodegradation of Phenolic Compounds - Karoyo, Abdalla H.; Yang, Jian; Wilson, Lee D. (Frontiers in Chemistry, 2018)
Dual function polymer materials with immobilized Sphingobium Chorophenolicum (SpC) bacterium cells are reported herein that undergo tandem adsorption and biodegradation of phenolic compounds. The cross-linked polymer materials contain β-cyclodextrin (β-CD) with incremental hexamethylene diisocyanate (HDI) cross-linker at variable mole ratios (X = 1, 3, or 6), denoted as HDI-X systems. The adsorptive uptake properties of the insoluble HDI-X polymers (X = 3 and 6) with various phenolic compounds [pentachlorophenol (PCP), 2,4,6-trichlorophenol (TCP), and 2,4,6-trimethylphenol (TMP)] were studied using batch adsorption isotherms. The molecular selective phenol removal (SR) capacity of the HDI-3 and HDI-6 materials was evaluated by electrospray ionization mass spectrometry (ESI-MS). The results were compared against granular activated carbon (GAC) and native β-CD, where 1D/2D 1H NMR spectral characterization of the complexes formed between phenolic guests and a soluble polymer (HDI-1) in aqueous solution provide insight on the intermolecular interactions and the role of cross-linking effects. Immobilization of SpC onto HDI-3 was shown to form a composite polymer/bacterium material. The composite system displays synergistic removal effects due to tandem PCP adsorption and SpC biodegradation to yield by-products such as 2,6-dichloro-1,4-hydroquinone (DCHQ). Apoptosis and cytotoxicity of DCHQ were evaluated using three breast cancer cell lines.